Effects of Supply Chain Security on Supermarkets Performance in Kenya (A case of Nakumatt supermarkets in Nairobi) - Nanyama, Everlyne; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
Ensuring a supply chain is secure from intentional as well as unintentional incidents is critical in today’s global economy. This study conceptualized and develops four supply chain security practices (trading partner security, procedural security, physical security and access control) and tested the relationships between the supply chain security and the performance of supermarkets in Kenya. The research adopted a descriptive design. The population of the study consisted of 120 employees from all Nakumatt branches in Nairobi. The study employed a census approach to collect data from the population of 120 respondents hence the study utilized 100% of the target population. Data for the study was collected and the findings were used to determine whether supply chain security can enhance supermarkets performance. Questionnaires were used as the main collection instrument and a pilot test was subsequently carried out to pre-test questionnaires for validity and reliability. The gathered data was analyzed using descriptive and inferential statistics aided by Statistical Package for Social Sciences (SPSS) version 20 and findings presented on tables, pie charts, figures and graphs. Correlation analysis and multiple regressions were used to establish the relationship between the research variables. The findings of the study suggest that access control, procedural security and physical security practices have a significant impact on supermarket performance. Thus the study recommended that management of the supermarkets should improve on provision of security awareness and training to its trading partners as this will help enhance the supply chain security culture. Also Total Security Management philosophy should be initiated to enhance supply chain security.